Strengthening the Uniqueness of Islamic Boarding Schools in Local Traditional Education in the Applicative Transformation of Multicultural Education - Yunita, Ratna; Soenjoto, Wening Purbatin Palupi; Nurhidayati, Maulida; Rahmawati, Rizqi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Islamic boarding schools, commonly known as pesantren, which have been established for a long time, require consistent teaching patterns and must face new problems that arise in adapting, such as the current technological era, without losing the uniqueness or distinctiveness of Islamic boarding schools as their character. Islamic boarding school is a place for deeper religious learning and is believed to bring blessings to students who study religion there. This study continues two previous studies on Islamic boarding schools and multicultural education in Islamic boarding schools by focusing more on the conditions of Islamic boarding schools, which are starting to lose their uniqueness due to the adaptation of government policies, the influence of technology, and responses to the development of demands for students whose diversity changes all the time. This study used a qualitative descriptive method with a phenomenological approach to solve problems and achieve research objectives. Data collection techniques were carried out through direct observation and in-depth interviews. The data obtained were then analyzed by the triangulation technique. The study results indicate that Islamic boarding schools face internal and external conflicts to maintain their existence in the era of technological change. Islamic boarding schools try not to change their uniqueness but face external demands as they accommodate students from different cultures, regions, languages, and even other countries who study religion. Even Islamic boarding schools cannot adapt to government regulations in determining policies for developing Islamic boarding schools in Indonesia.